Electrodeposition of co-doped hydroxyapatite coating on 316l stainless steel - Hanh, Vo Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Thanh, Dinh Thi Mai (Vietnam Journal of Science and Technology, 2018)
Hydroxyapatite (HAp) co-doped by magnesium (Mg), strontium (Sr), sodium (Na) and fluorine (F) were deposited on the 316L stainless steel (316L SS) substrate by electrodeposition method. The influences of scanning potential ranges, scanning times, scanning rates to form MgSrFNaHAp coating were investigated. The analytical results FTIR, SEM, Xray, EDX, thickness and adhension of the obtained coating at scanning potential ranges of 0 ÷ -1.7 V/SCE; scaning times of 5, scanning rate of 5 mV/s showed that MgSrFNaHAp coatings were single phase crystals of HAp, rod shape with the thickness 8.9 µm and the adhesion strength reached 8.38 MPa.